ANALISIS KELAYAKAN DAN RISIKO USAHATANI KENTANG DI DESA KUTABAWA KECAMATAN KARANGREJA KABUPATEN PURBALINGGA - Yusuf Enril Fathurrohman (Agritech: Jurnal Fakultas Pertanian Universitas Muhammadiyah Purwokerto, 2020)
This study aims to determine the feasibility of potatoes farming in Kutabawa Village, Karangeja District, Purbalingga Regency, and farming risks such as production, price, and income. The method used in this research is the descriptive analysis method with 30 respondents who were taken through the survey method. The results showed that the feasibility study was obtained by an R / C ratio of 2.33 or> 1 which indicated that potatoes farming in Kutabawa Village, Karangreja District, Purbalingga Regency were feasible with an average income of IDR 50,633,333 and a total cost of IDR 21,744,673. In terms of production and income, it has a high risk because it has a variation coefficient of more than 0.5 (0.7945 for production and 1.00895177 for income) and also a lower limit of production of -4123 kg and a lower limit of income of - Rp.29,405. 870 where it is less than 0. Whereas seen from the price aspect it has a coefficient of variation less than 0.5 (0.206965 <0.5) and also a lower limit of production of IDR 4253.71 where the farm will always profit or break even with an increase in the price of Rp. IDR 4253.71.